Measurement of the angular coefficients in [Zeta]-boson events using electron and muon pairs from data taken at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
The angular distributions of Drell-Yan charged lepton pairs in the vicinity of the Z-boson mass peak probe the underlying QCD dynamics of Z-boson production. This paper presents a measurement of the complete set of angular coefficients A 0−7 describing these distributions in the Z-boson Collins-Soper frame. The data analysed correspond to 20.3 fb−1 of pp collisions at s√=8 TeV, collected by the ATLAS detector at the CERN LHC. The measurements are compared to the most precise fixed-order calculations currently available (O(α2s)) and with theoretical predictions embedded in Monte Carlo generators. The measurements are precise enough to probe QCD corrections beyond the formal accuracy of these calculations and to provide discrimination between different parton-shower models. A significant deviation from the (O(α2s)) predictions is observed for A 0 − A 2. Evidence is found for non-zero A 5,6,7, consistent with expectations.
*The ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Im Titel ist [Zeta] als griechischer Buchstabe dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 02.06.2020